STK11 mutation impacts CD1E expression to regulate the differentiation of macrophages in lung adenocarcinoma - Qingfeng Zhang; Juan Feng; Kui Liu; Xiaoyan Yang; Yun Huang; Bo Tang (Immunity, Inflammation and Disease)
Abstract Background The deficiency of serine/threonine protein kinase 11 (STK11), one of the most common tumor suppressor genes in non‐small‐cell lung cancer, is a crucial player in tumor immune microenvironment regulation. This study attempted to unveil how mutated STK11 impact the differentiation of macrophages in lung adenocarcinoma (LUAD). Methods STK11 and CD1E expression levels in different cell models were assessed by quantitative reverse transcription polymerase chain reaction. Western blot was utilized to detect the protein expression levels of STK11, CD1E, apoptosis markers, and AMPK signaling pathway markers after transfection treatment. Cell viability and macrophage differentiation were detected by CCK‐8 and flow cytometry. Immunohistochemistry and immunofluorescence were employed to detect the expression of related genes and macrophage markers, respectively. Results This study found that STK11 mutations promoted the proliferation of LUAD cells and inhibited the differentiation of M1 macrophages, apoptosis, and the AMPK signaling pathway. Mutated STK11 led to CD1E downregulation, which curbed the differentiation of M1 macrophages and hence promoted LUAD progression. It was further validated by the in vivo experimental results that STK11 mutation significantly decreased the immune infiltration of M1 macrophages and promoted LUAD progression. Conclusion It was revealed that STK11 mutation affected CD1E expression to regulate macrophage differentiation in LUAD and then promote tumor progression. In this way, CD1E could be a potential biological target for the therapeutic interventions of STK11‐mutant LUAD patients. These findings also threw new light on a new therapeutic strategy for STK11‐mutant tumor patients that assisted the macrophage polarization pathway.